Evaluation of respiratory exposure to 4,4-methylene diphenyl diisocyanate (MDI) vapors in foam injection workers in a household appliance manufacturing company: An Occupational Carcinogen - Nikpey, Ahmad; Saeidabadi, Hamzeh; Sheikhi, Salman; Yari, Saeed; Jaddi Madarsara, Tayyebeh (Asian Pacific Journal of Environment and Cancer, 2019)
Background: Appliance manufacturing boom is very high hand customers always have a great deal of attention to products that have low energy consumption, therefore the use of isocyanates MDI as a thermal insulation in the body of the refrigerator and is also widely used as a binder in the production of washing machines. MDI isocyanate study the effects on the respiratory capacity of formers injection was done foam material in a household appliance company Method: this case control study in 1395 and a household appliance manufacturing company in the province of Qazvin 20 personnel working injected foam material is exposed to isocyanates ,for example administrative personnel and 20 served as controls using medical records these values breathing capacity FVC , FEV1 , FEV1/FVC in both 1390 and 1394 extracted using SPSS software and paired T-TEST data were analyzed. Results: Measuring the concentration of isocyanate in 90 blocks in the cabin and tap lid above the limit, which was due to the failure of the ventilation system, in 94 years due to the good performance of the ventilation system in the isocyanate concentration was at the limit. According to their experiences foam material is injected every three indexes FVC, FEV1, FEV1/FVC had significant losses, FEV1 and FVC decline among which were a significant level. (p=0.036, p= 0.008) the control samples also non- significant decline in the indicators that this can be attributed to aging. Conclusion: It is known that exposure to isocyanate materials decreased respiratory capacity is personnel, to postpone it to the desired function ventilation system. it would be desirable to postpone the operation of the ventilation system and non-isocyanate leak on the ground, work, be a lot of attention. even with the improvement of the job must be conservative’s injection foam material is exposed to isocyanates be included in the list of hard and hazardous jobs. Keywords: MDI, respiratory exposure, respiratory capacity, workers inject foam material.